Pelatihan Pembuatan Jamu Milenial untuk Cafe di Wisata Rainbow Garden Poetoek Soeko Trawas Mojokerto - Rani, Karina Citra; Eka Jayani, Nikmatul Ikhrom; Tandelilin, Elsye; Widjaja, Fitri Novika; Mukti, Yayon Pamula (LP2M INSURI Ponorogo, 2022)
Community service in the form of training on making millennial herbal medicine is carried out to increase the knowledge and skills of BUMDes Sukosari partners in processing millennial herbal drinks as a hallmark of the Rainbow Garden café. The method used in this PkM is the mentoring method or PAR (Participatory Action Research) with a lecture approach, product manufacturing practices, and guidance. The training is carried out in three stages: preparation, implementation, monitoring, and evaluation. The result of this training was an increase in partners' knowledge and skills in processing millennial herbal medicine, which was observed from the analysis of the mean test scores before and after the training (p <0.05). The output of this community service activity is five variants of millennial herbal drinks based on rhizomes and spices: Telang sparkling, Rosella sparkling, Curcuma sparkling, Curcuma milky, and Moringa milky. Community service activities regarding the processing of millennial herbal medicine in Sukosari Trawas Village provided skills for BUMDes partners to develop millennial herbal drink products of the Rainbow Garden Poetoek Soeko.